PREPARATION OF PHYTOSOME OF KERSEN LEAVES (Muntingia calabura L.) ETHANOL EXRTACT AS ANTIOXIDANT - Nur Illiyyin Akib; Nabila Saraswati Hendra; Andi Eka Purnama Putri; Indradewi Armadhani; Andi Nafisah Tendri Adjeng; Rifa’atul Mahmudah (Jurnal Farmasi Sains dan Praktis, 2021)
Kersen (Muntingia calabura L.) contains flavonoids that have the potential as antioxidants. However, its hydrophilic characteristics cause poor penetration so that its bioavailability is low. Research had been carried out on the preparation of ethanol extract of cherry leaves in ethosomal vesicle carriers. This study aimed to obtain the optimal phytosome suspension formula. Methods: Sample extraction was carried out by maceration method using ethanol as a solvent and was delipidated was by liquid-liquid method with n-hexane. The characterization of the extract included organoleptic, water-soluble extract content, ethanol soluble extract content, water content, ash content, acid insoluble ash content, and residual solvent. flavonoid contents were carried out by the TLC method and antioxidant activity was determined using DPPH method. Phytosome preparation was prepared by solvent evaporation and thin film hidration with ratio of extract and phosphatidylcholine 1:1 with concentration of 0.5% (A); 1% (B); and 1.5% (C). The characterization included observing morphology of vesicles using optical microscope, determining the size distribution of vesicles using PSA, and calculating the sorption efficiency using a spectrophotometer at max 281 nm. Results: The characteristics of extract were dark green; thick; distinctive aroma; ethanol soluble content were 70.91%; water soluble content were 32.5%; water content were 1.19%; ash content were 1.25%; acid insoluble ash content were 0.49%; and the remaining solvent was 0. The identification of flavonoids showed positive results. The extract has flavonoids and strong antioxidant activity with 62.71 g/mL for IC50. The shape is single layer large vesicle (LUV), diameter was 445.7 nm (A); 420.7 nm (B); and 419.6 nm (C). Vesicle entrapment efficiency was 5.83% (A); 47.575% (B); and 68.81% (C). It can be concluded that the optimal phytosome suspension formula is C with 1.5% phosphatidylcholine and 1.5% of extract.